2001
DOI: 10.1038/86243
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: To probe the structural basis for protein histidine kinase (PHK) catalytic activity and the prospects for PHK-specific inhibitor design, we report the crystal structures for the nucleotide binding domain of Thermotoga maritima CheA with ADP and three ATP analogs (ADPNP, ADPCP and TNP-ATP) bound with either Mg(2+) or Mn(2+). The conformation of ADPNP bound to CheA and related ATPases differs from that reported in the ADPNP complex of PHK EnvZ. Interactions of the active site with the nucleotide gamma-phosphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
110
0
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(119 citation statements)
references
References 45 publications
6
110
0
3
Order By: Relevance
“…We generated 20 different conformations of these two fragments using different initial velocities. The ATP lid loop ensemble was used to rule out effects associated to ATP lid flexibility, which has been extensively reported, even in the presence of ADP or non-hydrolysable ATP analogues (13,23,24). As for the four N-terminal residues in the ABD, allowed flexibility should take into account eventual effects of different initial dispositions on the final interdomain geometry.…”
Section: Methodsmentioning
confidence: 99%
“…We generated 20 different conformations of these two fragments using different initial velocities. The ATP lid loop ensemble was used to rule out effects associated to ATP lid flexibility, which has been extensively reported, even in the presence of ADP or non-hydrolysable ATP analogues (13,23,24). As for the four N-terminal residues in the ABD, allowed flexibility should take into account eventual effects of different initial dispositions on the final interdomain geometry.…”
Section: Methodsmentioning
confidence: 99%
“…This structural homology is remarkable given that only the ADP/ATP moiety was used to fit these molecules. In addition, x-ray structural studies have shown that there is extremely high structural homology within the ATP-binding pocket in the histidine kinases and ATPases (29).…”
Section: Fig 2 Alignment Of the Pdk2 Nucleotide-binding Domainmentioning
confidence: 99%
“…All necessary elements for histidine phosphorylation are found in the phosphotransfer (P1) and kinase (P4) domains of the five-domain CheA protein (4). Conserved residues in the P4 domain bind ATP in a pocket that optimally positions the ␥-phosphoryl for transfer to a specific histidine on the N-terminal P1 domain (4,5).…”
mentioning
confidence: 99%